SERVICES IN GRANTING BUILDING PERMITS AT THE INVESTMENT OFFICE AND ONE-STOP INTEGRATED SERVICES OF EAST LUWU REGENCY - Sakti, Nur Karya; Sakawati, Herlina; Nur, Andi Cudai (Jurnal Aktor, 2025)
This study aims to determine the quality of service in granting building permits at the Investment and One-Stop Services Office in East Luwu Regency. This research includes a qualitative approach descriptive research with data collection techniques through observation, interviews, literature study and documentation. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The results showed that the quality of service in granting building permits at the Investment and One Stop Service Office of East Luwu Regency based on the service quality indicators according to Zeithaml, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy was not fully qualified in providing services. The Tangible and Empathy indicators have been carried out well, but need to be optimized and need to be improved on the Reliability, Responsiveness and Assurance indicators because they are still not good. This is proven based on observations and interviews. The PBG/IMB issuance service process has been running well, although it is not yet optimal in providing timely guarantees and fast service because the PBG/IMB issuance process is sometimes late and the applicant has not been notified of the certainty of the waiting time